Behavioral strategy in perspective - Augier, Mie, 1972-; Lee, Christina; Rindova, Violina (Advances in strategic management, 2018)
Behavioral strategy has evolved as a field the last decades both intellectually and institutionally. This volume brings together scholars from several generations that have led and defined the behavioral approaches in strategy to reflect on the past, present,and future of behavioral strategy. Thus, rather than seeking empirical contributions that would fill in research gaps and expand research in specific domains, we endeavored to: a) represent the diversity of perspectives that inform behavioral research in strategic management; b) open up a space for reflection and provocation by scholars who are widely recognized as thought leaders both in their respective strands of behavioral strategy research, and in the field as a whole; and c) offer a set of perspectives and directions for the field of behavioral strategy at a pivotal moment in its evolution.